Unbiased Profiling Reveals Compartmentalization of Unconventional T-Cells Within the Intestinal Mucosa Irrespective of HIV Infection - Magnoumba, Magalli; Singh, Alveera; Ogongo, Paul; Roider, Julia; Asowata, Osaretin; Fehlings, Michael; Karim, Farina; Ndung'u, Thumbi; Anderson, Frank; Leslie, Alasdair; Kløverpris, Henrik (Frontiers in Immunology, 2020)
The intestinal mucosa is enriched for unconventional T-cells, including mucosal associated invariant T-cells (MAIT), invariant natural killer T-cells (iNKT) and γδ T-cells. These cells are activated by bacterial metabolites, lipid antigens and cytokines, and are important for intestinal barrier integrity. The loss of gut homeostasis observed in HIV infection is central to disease pathogenesis, and studies have highlighted impairment of particular unconventional T-cell subsets within a specific gut compartment. However, although the small and large intestine are distinct niches, the overall impact of HIV on unconventional T-cells across the gut mucosal has not been well studied. We hypothesised that compartment specific differences in the unconventional T-cell repertoire would exist between the small and large intestine, due to increasing bacterial loads and microbial diversity; and that the impact of HIV infection might differ depending on the compartment examined. We used mass cytometry, flow cytometry and unbiased T-cell receptor profiling to quantify unconventional T-cells in blood and tissue from the small (duodenum) and large (colon) intestine in HIV infected and uninfected participants undergoing examination for a range of intestinal conditions. Overall, we find distinct compartmentalisation of T-cells between blood, duodenum and colon, with iNKT cells significantly enriched in the duodenum and δ-1 expressing γδ T-cells in the colon. In addition, we observe greater clonal expansion of conventional TCRs in the duodenum, suggestive of stronger adaptive immunity in this compartment. Conversely, we find evidence of an expanded unconventional TCR repertoire in the colon, which contained far more overlapping “donor unrestricted” sequences than the duodenum. Twelve of these TCRs were highly “MAIT-like” and 3 were unique to the colon, suggesting an enrichment of donor unrestricted T-cells (DURTs) in this compartment. Unexpectedly, however, no significant impact of HIV infection on any of the unconventional T-cell subsets measured was observed in either mucosal site in terms of frequency or TCR repertoire. Further studies are required to investigate the importance of these unconventional T-cell subsets to intestinal homeostasis within the different gut compartments and determine if they are functionally impaired during HIV infection.